Diseño e implementación de un plan de mejora del sistema de seguridad y salud en el trabajo de un Terminal Marítimo en Cartagena de Indias (2020)
The research work presented below aims to design and implement a plan to improve the Health and Safety System at SG-SST work at a maritime terminal located in the city of Cartagena de Indias. The design and subsequent implementation of the improvement plan was carried out to mitigate the risks to which the organization's collaborators are exposed through compliance with the requirements necessary to ensure the quality of the services. For this, the findings and non-conformities of internal and external audits carried out between 2016 and 2019 were identified. The analysis of the identified problems was done through the root cause method for the formulation of corrective actions. At the end of the study, compliance with the corrective actions implemented was assessed, through management indicators to verify their compliance and effectiveness. The report includes the instruments for recording compliance with corrective actions.